PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN KOLABORASI SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 1 PUJIHARJO WONOGIRI - D.A. Siwi; Wijayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the collaboration skills of grade V students in learning Natural and Social Sciences (IPAS) at SD Negeri 1 Pujiharjo Wonogiri. Data collection methods were carried out by observation, tests, questionnaires, and documentation. The population in this study were all fifth grade students at SD Negeri 1 Pujiharjo Wonogiri, totaling 25 people. The research used quantitative methods with a pre-experimental design One Group Pretest-Posttest Design. The sample of this study was 25 fifth grade students with total sampling technique. The results were analyzed using paired sample t-test, which previously conducted Normality test as a prerequisite test with the help of SPSS 26. The results showed a significant difference between pretest and posttest scores (sig. = 0.018), as well as between conventional learning questionnaire results and PjBL model (sig. = 0.001), both <0.5. This finding proves that the application of the PjBL model can affect students' collaboration skills in IPAS learning.